PEMENUHAN HAK PEKERJA BANK BUMN SETELAH PEMUTUSAN HUBUNGAN KERJA YANG DISEBABKAN PELANGGARAN DISIPLIN: Studi Kasus Putusan Nomor 571 K/PDT.SUS/2010 - Immanuel Adventa Baragita Panunggal (2023)
An employee who is terminated from his job is obliged to receive his last rights as a token of gratitude from the company where he works which is useful as a saving for the employee's life. In fulfilling the rights of workers, each company has its own regulations or provisions that are adjusted to the provisions contained in the law. Bank BRI as a State-Owned Enterprise Bank (BUMN) also has its own provisions through company regulations regarding the granting of rights to workers who have experienced Termination of Employment (PHK). However, of course there are different things if the worker is terminated not because of full contract or assignment, but because of a disciplinary violation. Discipline violation. This research will discuss 2 issues, the first regarding how the rights received by state-owned bank workers when experiencing layoffs, and the second about how the implementation of the fulfillment of the rights of state-owned bank workers who were laid off due to disciplinary violations in Court Decision Number 571 K /PDT. SUS/2010? This study uses a normative juridical method with literature studies, a statutory approach, and a case approach through an analysis of the substance of court decisions. The conclusion of this study shows that workers who were laid off for committing disciplinary violations must still fulfill their rights by the company in accordance with applicable regulations, then in this decision the panel of judges also used the theory of justice in making their decisions regarding the rights of the defendant's layoffs regardless of regulations applicable laws.